2013
DOI: 10.1136/archdischild-2012-302695
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus abscesses: methicillin-resistance or Panton-Valentine leukocidin presence?

Abstract: Our study found a high prevalence of PVL presence in community-onset S aureus SSTIs in children in Spain. This toxin is associated with more abscess formation, regardless of methicillin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Some authors, mostly from the United States, have associated MRSA with more severe infections [7,8]. As previously reported, MRSA is presumably only a marker of severity by itself, and it is probably not as important in USA300 lowprevalence areas nor a significant independent predictor of severity [9,26].…”
Section: Discussionmentioning
confidence: 87%
“…Some authors, mostly from the United States, have associated MRSA with more severe infections [7,8]. As previously reported, MRSA is presumably only a marker of severity by itself, and it is probably not as important in USA300 lowprevalence areas nor a significant independent predictor of severity [9,26].…”
Section: Discussionmentioning
confidence: 87%
“…Several underlying reasons are offered for the finding, including reduced efficacy of many anti-MRSA antibiotics (Deresinski, 2007), delay in appropriate treatment because of failure to recognize MRSA infection (Kim et al, 2004), and the possibility that MRSA is more pathogenic compared to MSSA. Though the association of MRSA with increased pathogenicity has been suggested by several clinical studies, pertinent pathogenic factors have not been identified (Barrios Lopez et al, 2013, Watkins et al, 2012). In this study we demonstrated that PBP2A, the factor that makes MRSA resistant to β-lactam treatment, contributes to the pathogenicity of MRSA infection by changing PGN structure and augmenting immunopathology, although this effect is not observed until mecA is induced by β-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus is the leading cause of skin and soft tissue infections (SSTIs) in children, 1 and may cause bacteremia and other invasive diseases such as osteoarticular infections and pneumonia. 2 For the past 20 years, an increase in both community-associated and hospitalacquired infections by S. aureus has been observed, 3,4 causing significant morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%